A bibliometric analysis of T cell and atherosclerosis - Wei, Namin; Xu, Yan; Li, Ya’nan; Shi, Jingjing; Zhang, Xuesong; You, Yaping; Sun, Qianqian; Zhai, Huaqiang; Hu, Yuanhui (Frontiers in Immunology, 2022)
Atherosclerosis (AS) is widespread and develops into circulatory system problems. T cells play an essential regulatory role in AS occurrence and development. So far, there is no bibliometric research on T cells and AS. To learn more about T cell and AS development, 4,381 records were retrieved from Web of Science™ Core Collection. Then, these records were scientometrically analyzed using CiteSpace and VOSviewer in terms of spatiotemporal distribution, author distribution, subject categories, topic distribution, references, and keywords. Our analysis provides basic information on research in the field, demonstrates that the field has stabilized over the past decade, and identifies potential partners for interested researchers. Current research hotspots in this field mainly include the inflammatory mechanism, immune mechanism, related diseases, and related cytokines of AS. B cell, mortality, inhibition, and monocyte represent the frontiers of research in this field, undergoing an explosive phase. We hope that this work will provide new ideas for advancing the scientific research and clinical application of T cell and AS.